Investigation of the performance of RC beams reinforced with FRP and ECC materials - Sun, Guorui; Lai, Jie; Zheng, Yuzhou; Zheng, Kaikai; Shi, Jun (Journal of Civil Engineering and Management, 2022)
This paper investigates the structural working behavior of reinforced concrete beams bonded with fiber reinforced polymer and engineered cementitious composite materials subjected to bending using structural stressing state theory. First, six reinforced concrete beams externally bonded with composite reinforcement layer and one control beam are tested to investigate the effects of the bond length, fiber reinforced polymer grid thickness and fiber content on the flexural behavior. Then, the finite strain data of RC beams are interpolated by the numerical shape function method. The generalized strain energy density model is established to characterize the stressing state of the structure. Through the MannKendall criterion, the characteristics load P and Q of the beams are detected, and the whole loading process is divided into three stage. Finally, the analysis of the strain and deformation on the beams reveals the effect of different parameters on different stage. The characteristic load P increases as the bond length increases, and the characteristic load Q increases as the thickness of the FRP and the fiber content increase. The vertical deformation of the strengthened beam for the characteristic load Q and ultimate load is significantly smaller than that of the unreinforced beam.